2011
DOI: 10.3838/jjo.60.63
|View full text |Cite
|
Sign up to set email alerts
|

Chronological trends in the timing of spring bird migration and its relationship with temperature in a coastal forest near the city of Niigata

Abstract: . 2011. Chronological trends in the timing of spring bird migration and its relationship with temperature in a coastal forest near the city of Niigata. Jpn. J. Ornithol. 60: 63-72.Abstract. Chronological trends in the timing of spring bird migration and its relationship with temperature were studied in a coastal forest near the city of Niigata that is used by many migratory bird species. Analyses were conducted using median arrival dates for each bird species between 28 March and 11 June in the period 1989-200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Over the ensuing decades, consistent advances in spring migratory phenology (Bitterlin & Van Buskirk, 2014; Lehikoinen et al, 2019; Usui et al, 2017) have been found across Europe (Cotton, 2003; Newson et al, 2016; Saino et al, 2011; Sparks et al, 2005) and North America (Horton et al, 2020; Mayor et al, 2017; Zimova et al, 2021), and these advances are invariably linked to increases in global temperatures (Cotton, 2003; Horton et al, 2020; Hurlbert & Liang, 2012; Lehikoinen et al, 2019; Marra et al, 2005; Sparks et al, 2005). Variation exists within migratory birds, however, with greater phenological advances and tighter ties to vegetation phenology for short‐distance migrants compared to Neotropical, trans‐Saharan, or Southeast Asian migrants (Bitterlin & Van Buskirk, 2014; Horton et al, 2019; Hurlbert & Liang, 2012; Lehikoinen et al, 2019; Nakata et al, 2011; Tøttrup et al, 2012; Usui et al, 2017; Youngflesh et al, 2021; Zimova et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Over the ensuing decades, consistent advances in spring migratory phenology (Bitterlin & Van Buskirk, 2014; Lehikoinen et al, 2019; Usui et al, 2017) have been found across Europe (Cotton, 2003; Newson et al, 2016; Saino et al, 2011; Sparks et al, 2005) and North America (Horton et al, 2020; Mayor et al, 2017; Zimova et al, 2021), and these advances are invariably linked to increases in global temperatures (Cotton, 2003; Horton et al, 2020; Hurlbert & Liang, 2012; Lehikoinen et al, 2019; Marra et al, 2005; Sparks et al, 2005). Variation exists within migratory birds, however, with greater phenological advances and tighter ties to vegetation phenology for short‐distance migrants compared to Neotropical, trans‐Saharan, or Southeast Asian migrants (Bitterlin & Van Buskirk, 2014; Horton et al, 2019; Hurlbert & Liang, 2012; Lehikoinen et al, 2019; Nakata et al, 2011; Tøttrup et al, 2012; Usui et al, 2017; Youngflesh et al, 2021; Zimova et al, 2021).…”
Section: Introductionmentioning
confidence: 99%